Total Pancreatectomy With Islet Autotransplantation Resolves Pain in Young Children With Severe Chronic Pancreatitis. Issue 3 (March 2017) - Bellin, Melena D.; Forlenza, Gregory P.; Majumder, Kaustav; Berger, Megan; Freeman, Martin L.; Beilman, Gregory J.; Dunn, Ty B.; Pruett, Timothy L.; Murati, Michael; Wilhelm, Joshua J.; Cook, Marie; Sutherland, David E.R.; et al.
ABSTRACT: Objectives: Fear of diabetes and major surgery may prohibit referral of young children severely affected by pancreatitis for total pancreatectomy with islet autotransplant (TPIAT). We evaluated outcomes in our youngest TPIAT recipients, 3 to 8 years of age at surgery. Methods: Medical records were reviewed for 17 children (9 girls) ages 8 years or younger undergoing TPIAT from 2000 to 2014. Most (14/17) had genetic risk factors for pancreatitis. Since 2006, TPIAT recipients were followed prospectively with health questionnaires including assessments of pain and narcotic use, and scheduled hemoglobin A1c (HbA1c) and mixed-meal tolerance tests (6 mL/kg Boost HP) before surgery, and at regular intervals after. Patients are 1 to 11 years post-TPIAT (median 2.2 years). Data are reported as median (25th, 75th percentile). Results: All had relief of pain, with all 17 patients off narcotics at most recent follow-up. Hospitalization rates decreased from 5.0 hospitalization episodes per person-year of follow-up before TPIAT, to 0.35 episodes per person-year of follow-up after TPIAT. Fourteen (82%) discontinued insulin, higher than the observed insulin independence rate of 41% in 399 patients older than 8 years of age undergoing TPIAT over the same interval ( P = 0.004). Median post-TPIAT HbA1c was 5.9% (5.6%, 6.3%), and within patient post-TPIAT mean HbA1c was ⩽6.5% for all but 2 patients. Conclusions: Young children with severe refractory chronic pancreatitis may be good candidates for TPIAT, with high rates of pain relief and insulin independence, and excellent glycemic control in the majority. Abstract : Supplemental Digital Content is available in the text